Impact of GeoGebra on the Students’ Conceptual: Understanding of Limit of a Function in Bhutan - Kado Kado (International Journal of Asian Education, 2021)
The paradigm shift from traditional didactic instruction to technology-enriched teaching and learning environments significantly benefits learners. Educational technology can visualize abstract mathematical concepts contextually and graphically and allow learners to actively construct this knowledge. This study aims to ascertain the efficacy of a computer-assisted instruction method using GeoGebra in further developing the concept of the function limit for grade XI students. This study employed a quasi-experiment static-group comparison design with 60 students from Gongzim Ugyen Dorji Central School at Haa in Bhutan. The students were divided into two equal groups. Group ‘A’ used the GeoGebra software, while group ‘B’ used the conventional method to learn the limit of the function. The data was collected through a Conceptual Knowledge Test of Limit Function. In addition, an independent sample t-test was employed using the Statistical Package for the Social Sciences (SPSS 22.0). This study demonstrated that students who were taught using GeoGebra outperformed those who learned through conventional methods. The results confirmed that GeoGebra software could enhance and significantly improve students’ conceptual understanding of the limit of the function.